Effectiveness of school‐based strategies to prevent tooth decay in Filipino children: A cluster‐randomized trial. Issue 2 (2nd February 2022) - Ruff, Ryan Richard; Monse, Bella; Duijster, Denise; Itchon, Gina Santos; Naliponguit, Ella; Benzian, Habib
Abstract: Objectives: Evidence for affordable and pragmatic programmes to address the burden of untreated tooth decay in children in low‐ and middle‐income settings is limited. This study aimed to (1) assess the effect of a government‐run, school‐based daily group toothbrushing programme compared to standard school‐based oral health education on the incidence of dental caries and odontogenic infections in Filipino children over a period of 3 years; and (2) assess the additional preventive effect of on‐demand oral urgent treatment (OUT) and weekly fluoride gel application. Methods: A cluster‐randomized trial was conducted in Camiguin, Philippines. Schools in three regions were randomly assigned to one of three intervention groups: The Essential Health Care Programme (EHCP), which includes daily toothbrushing with fluoride toothpaste; EHCP plus twice‐yearly access to on‐demand urgent oral treatment (EHCP + OUT) and EHCP plus weekly application of high‐concentrated fluoride gel (EHCP + Fluoride). Schools in a nearby province with a similar child population were selected as external concurrent control group. Clinical oral examinations were performed by calibrated dentists from a random sample of 682 seven‐year‐old students who were examined at baseline and over the following 3 years. Outcome variables were the number of decayed primary teeth, the number of decayed, missing and filled permanent teeth (DMFT) and surfaces (DMFS), and the number of permanent teeth with pulpal involvement, ulcerations, fistula or abscess (PUFA). Data were analysed using multilevel mixed‐effects negative binomial regression. Results: Three years after implementation, increments in dental caries and odontogenic infections in permanent teeth did not significantly differ between the EHCP and control group, yet the incidence of DMFT was lower by 22% in children receiving EHCP. Compared to controls, children receiving EHCP + Fluoride had a significantly lower increment of DMFT, DMFS and PUFA by 40%, 40% and 47%, respectively. Children receiving EHCP + OUT had lower incidence rates of DMFT and DMFS than control children by 23% and 28%, respectively. A lower incidence rate was also found for PUFA, but the effect was not statistically significant. Conclusions: Findings suggest that the weekly application of fluoride gel and urgent oral treatment, in addition to daily school‐based toothbrushing with fluoride toothpaste, are realistic and effective strategies to lower the burden of dental caries in Filipino children. Implementation challenges may explain why no substantial caries‐preventive benefits were demonstrated for school‐based toothbrushing only. Intervention compliance should be considered in future programme implementation and evaluation research.